(untitled) (Clinical Sociology Review, 2025)
This article addresses the question of how to take anthropologists’ subjectivity into account in their research through a psychoanalytically oriented clinical approach. Through the analysis of the author’s own psychological movements, he hypothesizes that a sense of guilt may be common to those who practice anthropology, and that analyzing their transference and countertransference reactions can provide a way to access the reality of the other. In this way, he proposes to find in the clinical approach an ethic that allows us to break with the evolutionary and neocolonial positions of the discipline. He seeks to define anthropology as the practice of intercultural dialogue, first at the level of intersubjectivity, but also at the level of culturally distant social and institutional practices.